International motifs and plots in the Kazakh epics in China (on the materials of the Kazakh epics in China) - Abikhanova, Gulzhanat; Ahmetbekova, Akbota; Bayat, Erbolat; Donbaeva, Ainur; Burkitbay, Gaukhar (Opción, 2018)
The article outlines the international motifs and plots used in the Kazakh epics in China. Part of our compatriots living in more than forty countries reside the People's Republic of China. It has been discovered that our Chinese counterparts have retained their ethnic identity, language, religion, national culture, traditions, customs and folklore, even though they have experienced a lot of disasters. The heritage of Kazakhs in China has been studied before. But the Kazakh epics have been examined for the first time.